Wedding Photography Marketing Communication Analysis: Analisis Komunikasi Pemasaran Fotografi Pernikahan - Muhammad Yhattaqun; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2022)
The era of globalization has given birth to increasingly fierce competition among companies, organizations or individuals who are currently doing business or are running a business, whether it's a business in the field of culinary, services, furniture and so on. Efficient and effective communication is needed to be able to convey ideas, thoughts, and feelings to all consumers, including the photography business. The photography business began to mushroom in the community who also needed to capture moments with family, partners or companies. The photo and video production house “Moonrise Photowork” is an example of a photography business that is developing in the community, especially in Sidoarjo Regency and Surabaya City. The purpose of this study was to determine the marketing communications carried out by